Hypertension of liver-yang hyperactivity syndrome induced by a high salt diet by altering components of the gut microbiota associated with the glutamate/GABA-glutamine cycle - Zheng, Tao; Wu, Yi; Peng, Mai-jiao; Xiao, Nen-qun; Tan, Zhou-jin; Yang, Tao (Frontiers in Nutrition, 2022)
The gut microbiota and metabolites are closely related to hypertension; however, the changes in the composition of the gut microbiome and metabolites linking a high salt diet to elevated blood pressure are not established. In this study, traditional Chinese medicine(TCM) syndrome of hypertension caused by high salt had been diagnosed and the pathogenesis of hypertension was explored from the perspective of intestinal microecology. Rats in a high salt diet-induced hypertension group (CG) and normal group (CZ) were compared by 16S rRNA gene full-length sequencing and liquid chromatography and mass spectrometry to identify differences in the bacterial community structure, metabolites, and metabolic pathways. Hypertension induced by a high salt diet belongs to liver-Yang hyperactivity syndrome. Alpha and beta diversity as well as the composition of microbiota from the phylum to species levels differed substantially between the CG and CZ groups. In an analysis of differential metabolites in the intestines, a high salt diet mainly affected the metabolism of amino acids and their derivatives; in particular, γ-aminobutyric acid (GABA) was down-regulated and glutamic acid and its derivatives were up-regulated under a high salt diet. Based on a KEGG analysis, high salt intake mainly altered pathways related to GABA and the glutamate/glutamine metabolism, such as the GABAergic synapse pathway and glutamatergic synapse pathway. The correlation analysis of differential gut microbes and differential metabolites suggested that a high salt diet promoted hypertension via the inhibition of Clostridiaceae_1 growth and alterations in the GABA metabolic pathway, leading to increased blood pressure. These findings suggest that a high salt diet induces hypertension of liver-Yang hyperactivity syndrome by mediating the microbiota associated with the glutamate/GABA-glutamine metabolic cycle via the gut–brain axis.